2022
DOI: 10.3389/fimmu.2022.807682
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Ecological Implications of Microbiota Diversity in Birds: Natural Barriers Against Avian Malaria

Abstract: Natural antibodies (Abs), produced in response to bacterial gut microbiota, drive resistance to infection in vertebrates. In natural systems, gut microbiota diversity is expected to shape the spectrum of natural Abs and resistance to parasites. This hypothesis has not been empirically tested. In this ‘Hypothesis and Theory’ paper, we propose that enteric microbiota diversity shapes the immune response to the carbohydrate α-Gal and resistance to avian malaria. We further propose that anti-α-Gal Abs are transmit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 100 publications
0
8
0
Order By: Relevance
“…For example, bacteria within the family Enterobacteriaceae are a rich source of α1,3-galactosyltransferase (α1,3GT) activity. Immune response to the carbohydrate α-Gal on the surface of microbiota bacteria in birds could trigger anti-α-Gal antibodies [ 7 ], with malaria killing activity [ 78 ]. Interestingly, the abundance of Escherichia-Shigella was significantly reduced in P. homocircumflecxum -infected birds at 24 DPI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, bacteria within the family Enterobacteriaceae are a rich source of α1,3-galactosyltransferase (α1,3GT) activity. Immune response to the carbohydrate α-Gal on the surface of microbiota bacteria in birds could trigger anti-α-Gal antibodies [ 7 ], with malaria killing activity [ 78 ]. Interestingly, the abundance of Escherichia-Shigella was significantly reduced in P. homocircumflecxum -infected birds at 24 DPI.…”
Section: Discussionmentioning
confidence: 99%
“…The local habitat of the birds was also shown to have a large influence on gut microbiome composition in Arctic-breeding shorebirds [ 5 ], and Brown-headed Cowbirds [ 6 ]. The ecological implications of microbiota diversity in wild birds remain to be explored [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our study is among the first to assess correlates between malaria infection and microbiome composition in avian hosts sampled in a natural system. The volume of research supporting critical connections between microbiomes and malaria susceptibility and severity in mammals is steadily growing (Bamgbose et al, 2021); however, little comparable research has been conducted in other host taxa or in wild environments (Trevelline et al, 2019; but see Lutz et al, 2021; Palinauskas et al, 2022; Videvall, Marzal, et al, 2021). We found no difference in cloacal microbiome alpha diversity between Hawaiʻi ʻamakihi and warbling white‐eyes and only a small, yet significant, difference in beta diversity, which aligns with several studies that have reported few consistent differences across host species that are relatively close phylogenetically (Hird et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Cloacal and faecal microbiomes are not perfect representatives of the microbial community in other regions of the gut (Videvall et al, 2018), and despite the added challenge, sampling the ileum, caecum or colon in laboratory experiments may reveal stronger associations between commensal microbes and infection response. Field studies that concentrate efforts on resampling individuals over time or controlled laboratory experiments (such as proposed in Palinauskas et al, 2022) would facilitate tracking microbiome changes over the course of infection, and potentially also the sampling of microbiomes of birds that succumb to malaria, which was not possible for our study. We used cross‐sectional comparisons between chronically infected survivors and uninfected, malaria‐naïve ʻamakihi, as well as comparisons with a malaria‐resistant species, to identify microbes that may be associated with malaria immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Production of anti-a-Gal Abs in humans is thought to be driven by intestinal exposure to bacteria of the Klebsiella, Serratia, and Escherichia genera expressing a-Gal (61). In addition to these bacterial genera, a1,3-GT genes are broadly distributed in the bacterial gut microbiome of humans (63), and wild and domestic birds (64). In this study, some of these bacterial taxa were found to contribute to the pool of a1,3-GT genes in the microbiome of the penguins E. chrysolophus, E. minor, P. papua, A. patagonicus, and S. humboldti.…”
Section: Discussionmentioning
confidence: 99%